Control Environment, Financial Accountability and Financial Reporting Quality in Uganda’s Public Sector - Noowe Nelson; John Baguma Muhunga Kule; Sowedi Kambale; Angee Gladys (International Journal of Finance and Accounting, 2026)
This paper investigates how Control Environment (CE) and Financial Accountability (FA) influence Financial Reporting Quality (FRQ) in the public-sector institutions in South-Western Uganda, a context where public institutions face persistent financial reporting inaccuracies and delays. This was a cross-sectional quantitative study involving structured questionnaires distributed to 96 public officials across various public sector entities in Uganda. Data were analysed through correlation and also regression analyses, employing Baron and Kenny’s (1986) four-step approach for mediation, with significance of indirect effect assessed using the Sobel test. The research study results show that CE plays a key strong CE have improved ethical leadership, audit oversight, and clearly defined roles that allow for accurate and timely reporting. The study results revealed that public sector institutions with strong governance structures were more likely to uphold transparency and responsible financial behaviour, highlighting the contingent role of CE in explaining FA to public stakeholders. The results indicated a positive association between FA and FRQ, implying that public sector institutions that practice expenditure tracking, documentation, and ethical compliance were likely to produce more credible financial reports. The mediation analysis revealed that FA partially mediated the association between CE and FRQ, which suggested that CE can accurately influence FRQ through FA. This study makes a unique contribution by incorporating the agency theory (AT) and also the stewardship theory (ST) in the examination of FRQ in public sector institutions, a sector where the quality of financial reports is inherently linked to managerial accountability towards organisational goals and the safeguarding of stakeholder interests. The research study demonstrates that CE not only enhance FRQ directly but also has an influence on the upholding of transparency and responsible financial behaviour that supports public sector institutions to prepare and present financial reports on an accurate, timely and consistent basis. The study advocates that public institutionsinvest in training programs that reinforce ethical leadership, effective audit committees and enhance FA mechanisms, ultimately improving public sector institution FRQ.
Keywords: Control environment; Financial; Accountability; Financial reporting; Public sector; Reporting quality.